Introduction of smart technologies in event-management: socio-cultural aspect - V. A. Shelginskaya (Цифровая социология)
The event industry is currently undergoing a period of active social change and technological innovation driven by the approach of the fourth industrial revolution and the advent of new methods of data processing by artificial intelligence. This could provide the meeting industry with new management capabilities related to the ability to predict and program visitor behavior based on the analysis of extremely large amounts of data about their behavior, thinking and preferences. However, event activities are based on creating for the visitor such a spatio-temporal period that he perceives as unique. This makes event technologies an effective tool for achieving commercial, communication or image goals of an organization. The specificity of creating this uniqueness is largely related to the socio-communicative and aesthetic-axiological aspects of human life. Therefore, for the sustainable development of an event organization, it is important not only to keep pace with advanced technological developments, but also to take into account anthropological specifics, the influence of “smart” processes on which has not been sufficiently studied, and potential risks need to be clarified.   The purpose of the study is to assess how the event activity will change if its content fully corresponds to the life habits and behavior of the client. To achieve this goal, the principles of systemic and comparative analysis were used.   The empirical base of the study is the data of the survey of respondents, as well as the results of previous studies in this area. The study is of interest to specialists in the field of sociology, anthropology and management, as well as to those in the event industry.